PERAN GURU DALAM MENINGKATKAN KUALITAS PENDIDIKAN ISLAM - Mu?arif, Syamsul (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Unemployment is a scourge for education, low national exam scores are a disgrace to school, free association and crime are the failure of parents and teachers in educating. Therefore, providing quality education is a necessity. This study aims to analyze teachers influence in improving the quality of education. The research method uses quantitative, the object of research is AL-Amanah Al-Gontory South Tangerang, the research sample is the teacher, and the sample technique uses a census. The results showed those discipline, leadership, motivation has significant effect on the quality of Islamic education, both partially and simultaneously. This means, The teacher is the main key in improving the quality of education, this is clearly reflected in students' morals and academic achievements, and and in the future it has an impact on personal character